Recurrence of drug‐induced reactions in DRESS patients. (13th March 2014) - Picard, D.; Vellar, M.; Janela, B.; Roussel, A.; Joly, P.; Musette, P.
Abstract: Background: Drug reaction with eosinophilia and systemic symptoms (DRESS) may relapse following introduction of drugs structurally unrelated to the initial culprit drug. Objective: To assess the frequency and characteristics of recurrent drug eruptions in patients with history of DRESS. Methods: Patients who had developed adverse cutaneous reaction after DRESS occurrence were recruited from the regional database of Upper Normandy in France. Rate of recurrences were compared with patients with Toxic Epidermal Necrolysis (TEN) and Stevens–Johnson syndrome (SJS) patients during the same time frame. Results: Of the 60 cases of DRESS collected, 15 (25%) with recurrences were retained for analysis. Seven patients had a single recurrence, whereas eight patients had several relapses. In the patients with pre‐existing DRESS, recurrences were incomplete, corresponding to cutaneous rash in 13 cases and associated with eosinophilia in seven cases. Internal organ involvement was observed in two cases. In contrast, a single recurrence was found out of 61 patients with TEN/SJS. Conclusion: Incomplete recurrences with structurally unrelated culprit drugs are a frequent phenomenon in DRESS patients.